SEASONAL INFLUENCE ON THE HELMINTH INFECTION IN CHANNA PUNTATUS - LEELA, B.; BABU, V. SURESH; RAMULU, G. RAGHU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The present investigation includes understanding of the ecology and biology of helminthes for better treatment of fish infections. Seasonal variations cause fluctuations in the population of arthopods and molluscans which act as intermediate hosts for helminthes. Thus, the infections in fishes vary with population levels of the intermediate hosts. This preliminary survey is presented in quantified form and discussed in view of the earlier works.